Pengaruh Kinerja Baterai Mobil Listrik LAKSAMANA V2 Terhadap Variasi Kecepatan Dan Beban Kendaraan Menggunakan Simulink - Kafaj, M. Al; Setyawan, Reinaldi Teguh; Umira, Siti (P3M Politeknik Negeri Jember, 2025)
Battery performance is a crucial factor in determining the efficiency and driving range of electric vehicles. This study aims to analyze the effect of battery performance on variations in vehicle speed and load using MATLAB/Simulink simulation modeling. The developed simulation model reflects the real operational conditions of the Laksamana V.2 electric vehicle, with key parameters including a 48V battery voltage, 2 kW motor, and varying vehicle loads. Simulations were carried out at different speeds ranging from 20 km/h to 60 km/h under two conditions: unloaded and fully loaded. The results show that power consumption increases with higher speed and load. The simulation also reveals that the total battery energy gradually decreases over time due to fluctuating current consumption. Motor torque is higher at lower speeds and tends to decrease at higher speeds. The system’s maximum efficiency reaches 83.8% at 55 km/h under no-load conditions. These findings indicate that speed and load variations significantly affect battery performance and energy efficiency, and that Simulink modeling is effective in visualizing and evaluating the behavior of electric vehicle systems comprehensively.